Peran Manajemen Kurikulum Merdeka terhadap Kinerja Guru - Wathon, A (ISLAMIKA, 2025)
Curriculum Management in the Merdeka Curriculum plays an important role in improving teacher performance in Indonesia, especially in the context of implementing a curriculum that is more flexible and based on the needs of students. The background of this research is driven by the challenges in implementing the Merdeka Curriculum, which requires significant adjustments in teachers' teaching approaches and classroom management. This study uses a qualitative method to explore teachers' perceptions and experiences regarding the implementation of the curriculum and its impact on their performance. Data collection techniques were carried out through in-depth interviews and observations in several schools that have implemented the Merdeka Curriculum. The results show that good curriculum management, including thorough planning, continuous training, and support from the school, can enhance teachers' understanding of the curriculum and creativity in developing effective teaching strategies. However, some challenges, such as time and resource limitations, still affect teachers' performance in implementing the curriculum. In conclusion, effective curriculum management plays a significant role in supporting teacher performance, but more intensive collaboration between various parties is needed to overcome existing challenges and improve the effectiveness of the Merdeka Curriculum implementation.